ANALISIS KEKUATAN STRUKTUR SQUARE CHAMBER INJECTION MULTICASTING PYROGENIC IGNITER MENGGUNAKAN FINITE ELEMENT ANALYSIS (FEA) - Prayoga, Rama Dwi; Prasetyo, Ichsan Dwi; Mahdiyyah, Maharani Inas (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Brawijaya, 2024)
It is necessary to analyze the structural strength of the square chamber component in the design of injection multicasting pyrogenic igniter to ensure that the structural components of the chamber are able to withstand loads from hydraulic piston pressure. Four square chamber configurations were analyzed using the Autodesk Inventor software FEA method. Load simulations are given at 10,000 N, 50,000 N, and 100,000 N. Von Mises stress, safety factor, and displacement are obtained for each design configuration. Where it is known that the structural design of the square chamber design configurations 1, 2, and 3 has optimal reliability at a load capacity of up to ± 10,000 N. As for the structural design of the square chamber design configuration 4, it is known to have optimal reliability at a load capacity of 50,000 N. However it is possible that it is reliable enough to withstand load capacities up to ± 100,000 N.